Monoterpenes Differently Regulate Acid-Sensitive and Mechano-Gated K2P Channels - Eden Arazi; Galit Blecher; Noam Zilberberg; Noam Zilberberg (Frontiers Media S.A., 2020)
Potassium K2P ("leak") channels conduct current across the entire physiological voltage range and carry leak or "background" currents that are, in part, time- and voltage-independent. The activity of K2P channels affects numerous physiological processes, such as cardiac function, pain perception, depression, neuroprotection, and cancer development. We have recently established that, when expressed in Xenopus laevis oocytes, K2P2.1 (TREK-1) channels are activated by several monoterpenes (MTs). Here, we show that, within a few minutes of exposure, other mechano-gated K2P channels, K2P4.1 (TRAAK) and K2P10.1 (TREK-2), are opened by monoterpenes as well (up to an eightfold increase in current). Furthermor\e, carvacrol and cinnamaldehyde robustly enhance currents of the alkaline-sensitive K2P5.1 (up to a 17-fold increase in current). Other members of the K2P potassium channels, K2P17.1, K2P18.1, but not K2P16.1, were also activated by various MTs. Conversely, the activity of members of the acid-sensitive (TASK) K2P channels (K2P3.1 and K2P9.1) was rapidly decreased by monoterpenes. We found that MT selectively decreased the voltage-dependent portion of the current and that current inhibition was reduced with the elevation of external K+ concentration. These findings suggest that penetration of MTs into the outer leaflet of the membrane results in immediate changes at the selectivity filter of members of the TASK channel family. Thus, we suggest MTs as promising new tools for the study of K2P channels' activity in vitro as well as in vivo.